Reactions in non-aqueous alkali and alkaline-earth metal–oxygen batteries: a thermodynamic study. Issue 42 (26th October 2021) - Pierini, Adriano; Brutti, Sergio; Bodo, Enrico
Abstract : The disproportionation of alkali and alkaline-earth metal superoxide is investigated using multiconfigurational methods. Abstract : Multivalent aprotic metal–oxygen batteries are a novel concept in the applied electrochemistry field. These systems are variants of the so-called Li–air batteries and up to present are in their research infancy. The superoxide disproportionation reaction is a crucial step for the operation of any metal–oxygen redox system using aprotic solvents: in the best scenario, disproportionation leads to peroxide formation while in the worse one it releases singlet molecular oxygen. In this work we address the fundamental thermodynamics of such reaction for alkali (Li, Na and K) and alkaline earth (Be, Mg and Ca) metal–O2 systems using multiconfigurational ab initio methods. Our aim is to draw a comprehensive description of the disproportionation reaction from superoxides to peroxides and to provide the thermodynamic likelihood of the pathways to singlet oxygen release.